A PI3Kγ signal regulates macrophage recruitment to injured tissue for regenerative cell survival. (21st September 2022) - Zhou, Siyu; Liu, Zhengcheng; Kawakami, Atsushi
Abstract: The interaction between immune cells and injured tissues is crucial for regeneration. Previous studies have shown that macrophages attenuate inflammation caused by injuries to support the survival of primed regenerative cells. Macrophage loss in zebrafish mutants like cloche ( clo ) causes extensive apoptosis in the regenerative cells of the amputated larval fin fold. However, the mechanism of interaction between macrophage and injured tissue is poorly understood. Here, we show that a phosphoinositide 3‐kinase gamma (PI3Kγ)‐mediated signal is essential for recruiting macrophages to the injured tissue. PI3Kγ inhibition by the PI3Kγ‐specific inhibitor, 5‐quinoxalin‐6‐ylmethylene‐thiazolidine‐2, 4‐dione (AS605240 or AS), displayed a similar apoptosis phenotype with that observed in clo mutants. We further show that PI3Kγ function during the early regenerative stage is necessary for macrophage recruitment to the injured site. Additionally, protein kinase B (Akt) overexpression in the AS‐treated larvae suggested that Akt is not the direct downstream mediator of PI3Kγ for macrophage recruitment, while it independently plays a role for the survival of regenerative cells. Together, our study reveals that PI3Kγ plays a role for recruiting macrophages in response to regeneration.